THE IMPACT OF DIGITAL LEARNING LICENSES ON ACCESS TO EDUCATION IN PRIMARY SCHOOLS: A LITERATURE REVIEW - Ramadhani Lubis, Renni; Mariana Parinduri, Wina; Rahmayanti Rambe, Titin; Rambe, Nurhamimah; Fadli, Muhammad (Universitas Negeri Medan, 2024)
This research aims to analyze and identify various previous research results related to the impact of digital learning licenses on access to education in elementary schools. This research is qualitative research using a literature review approach. The data used in this research are scientific articles and journals that are relevant to the research topic. The data sources selected include research published within the last 5 years, which discusses issues related to digital learning licensing, educational access, and technology implementation at the basic education level. The data collection technique used is through academic databases such as Google Scholar, JSTOR, ProQuest, and so on. By using keywords such as